Effectiveness Of Health Education About The Dangers Of Cigarettes On The Intention To Stop Smoking Among Adolescents - Rizky Rahadian Wicaksono; Sutriyati Sutriyati; Rahmat Pannyiwi (International Journal of Health Sciences, 2025)
Background: Smoking among adolescents remains a serious public health problem in Indonesia. Adolescents are a vulnerable group easily influenced by their environment and cigarette advertising. Health education is an effective way to raise awareness and foster the intention to quit smoking. Objective: This study aims to determine the effectiveness of health education about the dangers of smoking on the intention to quit smoking in adolescents. Method: This study used a pre -experimental design with a one-way design. group pretest – posttest. The sample consisted of 40 active adolescent smokers selected using purposive sampling technique at State Senior High School X. Counseling was provided for 60 minutes using interactive lecture methods and educational videos. The research instrument was an Intention questionnaire. to Quit Smoking The IQSS scale has been tested for validity and reliability. Data analysis used a paired t- test to examine differences in smoking cessation intentions before and after the intervention. Results: The average smoking cessation intention score before the intervention was 52.3, increasing to 76.1 after the counseling. The statistical test results showed a p- value of 0.000 (<0.05), which means there was a significant difference between the pretest and posttest. Conclusion: Health education about the dangers of smoking has been proven effective in increasing adolescents' intention to quit smoking. It is hoped that education programs will be implemented regularly in schools to foster healthy lifestyles in the younger generation.